Myocardial Adaptations to Recreational Marathon Training Among Middle-Aged Men. (February 2015) - Zilinski, Jodi L.; Contursi, Miranda E.; Isaacs, Stephanie K.; Deluca, James R.; Lewis, Gregory D.; Weiner, Rory B.; Hutter, Adolph M.; d'Hemecourt, Pierre A.; Troyanos, Christopher; Dyer, K. Sophia; Baggish, Aaron L.
<x xml:space="preserve">Abstract</x> Background— Myocardial adaptations to exercise have been well documented among competitive athletes. To what degree cardiac remodeling occurs among recreational exercisers is unknown. We sought to evaluate the effect of recreational marathon training on myocardial structure and function comprehensively. Methods and Results— Male runners (n=45; age, 48±7 years; 64% with ≥1 cardiovascular risk factor) participated in a structured marathon-training program. Echocardiography, cardiopulmonary exercise testing, and laboratory evaluation were performed pre and post training to quantify changes in myocardial structure and function, cardiorespiratory fitness, and traditional cardiac risk parameters. Completion of an 18-week running program (25±9 miles/wk) led to increased cardiorespiratory fitness (peak oxygen consumption, 44.6±5.2 versus 46.3±5.4 mL/kg per minute; P<0.001). In this setting, there was a significant structural cardiac remodeling characterized by dilation of the left ventricle (end-diastolic volume, 156±26 versus 172±28 mL, P<0.001), right ventricle (end-diastolic area=27.0±4.8 versus 28.6±4.3 cm2; P=0.02), and left atrium (end-diastolic volume, 65±19 versus 72±19; P=0.02). Functional adaptations included increases in both early (E′=12.4±2.5 versus 13.2±2.0 cm/s; P=0.007) and late (A′=11.5±1.9 versus 12.2±2.1 cm/s; P=0.02) left ventricular diastolic velocities. Myocardial remodeling was accompanied by beneficial changes in cardiovascular risk factors, including body mass index (27.0±2.7 versus 26.7±2.6 kg/m2; P<0.001), total cholesterol (199±33 versus 192±29 mg/dL; P=0.01), low-density lipoprotein (120±29 versus 114±26 mg/dL; P=0.01), and triglycerides (100±52 versus 85±36 mg/dL; P=0.02). Conclusions— Among middle-aged men, recreational marathon training is associated with biventricular dilation, enhanced left ventricular diastolic function, and favorable changes in nonmyocardial determinants of cardiovascular risk. Recreational marathon training may, therefore, serve as an effective strategy for decreasing incident cardiovascular disease.